Validation of lactate level as a predictor of early mortality in acute decompensated heart failure patients who entered intensive care unit. Issue 2 (February 2015) - Kawase, Tomoharu; Toyofuku, Mamoru; Higashihara, Tasuku; Okubo, Yousaku; Takahashi, Lisa; Kagawa, Yuzo; Yamane, Kenichi; Mito, Shinji; Tamekiyo, Hiromichi; Otsuka, Masaya; Okimoto, Tomokazu; Muraoka, Yuji; et al.
Abstract: Background: The significance of routine measurement of lactate level is unclear in patients with critical acute decompensated heart failure (ADHF). Methods and results: Consecutive 754 patients who were admitted to the intensive care unit (ICU) in our hospital from January 2007 to March 2012 and given a diagnosis of ADHF were eligible for retrospective entry into the registry. Lactate level was measured on admission from routine arterial blood sample and we investigated by comparing the lactate level and parameters of conventional in-hospital mortality predictors. Among the patients, 88 (12%) died during hospitalization. The lactate level had great power to predict in-hospital mortality, as suggested by the c -statistics of 0.71. The occurrence of in-hospital death was more pronounced in patients with high levels of lactate (>3.2 mmol/l) and the tendency was observed in patients in both the acute coronary syndrome (ACS) group and non-ACS group. In multivariate analysis, elevated lactate levels remained an independent predictor of in-hospital death (odds ratio, 2.14; 95% confidence interval, 1.10–4.21; p = 0.03). Conclusions: Elevated levels of arterial lactate on admission were related to worse in-hospital mortality in patients with ADHF either with or without ACS, suggesting that the presence of high lactate in patients who enter the ICU with ADHF could help stratify the initial risk of early mortality.